Repetitive Elements Contribute to the Diversity and Evolution of Centromeres in the Fungal Genus Verticillium - Michael F. Seidl (American Society for Microbiology, 2020)
ABSTRACT Centromeres are chromosomal regions that are crucial for chromosome segregation during mitosis and meiosis, and failed centromere formation can contribute to chromosomal anomalies. Despite this conserved function, centromeres differ significantly between and even within species. Thus far, systematic studies into the organization and evolution of fungal centromeres remain scarce. In this study, we identified the centromeres in each of the 10 species of the fungal genus Verticillium and characterized their organization and evolution. Chromatin immunoprecipitation of the centromere-specific histone CenH3 (ChIP-seq) and chromatin conformation capture (Hi-C) followed by high-throughput sequencing identified eight conserved, large (∼150-kb), AT-, and repeat-rich regional centromeres that are embedded in heterochromatin in the plant pathogen Verticillium dahliae. Using Hi-C, we similarly identified repeat-rich centromeres in the other Verticillium species. Strikingly, a single degenerated long terminal repeat (LTR) retrotransposon is strongly associated with centromeric regions in some but not all Verticillium species. Extensive chromosomal rearrangements occurred during Verticillium evolution, of which some could be linked to centromeres, suggesting that centromeres contributed to chromosomal evolution. The size and organization of centromeres differ considerably between species, and centromere size was found to correlate with the genome-wide repeat content. Overall, our study highlights the contribution of repetitive elements to the diversity and rapid evolution of centromeres within the fungal genus Verticillium. IMPORTANCE The genus Verticillium contains 10 species of plant-associated fungi, some of which are notorious pathogens. Verticillium species evolved by frequent chromosomal rearrangements that contribute to genome plasticity. Centromeres are instrumental for separation of chromosomes during mitosis and meiosis, and failed centromere functionality can lead to chromosomal anomalies. Here, we used a combination of experimental techniques to identify and characterize centromeres in each of the Verticillium species. Intriguingly, we could strongly associate a single repetitive element to the centromeres of some of the Verticillium species. The presence of this element in the centromeres coincides with increased centromere sizes and genome-wide repeat expansions. Collectively, our findings signify a role of repetitive elements in the function, organization, and rapid evolution of centromeres in a set of closely related fungal species.